2004
DOI: 10.1128/mcb.24.17.7622-7635.2004
|View full text |Cite
|
Sign up to set email alerts
|

Internal Ribosome Entry Site Structural Motifs Conserved among Mammalian Fibroblast Growth Factor 1 Alternatively Spliced mRNAs

Abstract: Fibroblast growth factor 1 (FGF-1) is a powerful angiogenic factor whose gene structure contains four promoters, giving rise to a process of alternative splicing resulting in four mRNAs with alternative 5 untranslated regions (5 UTRs). Here we have identified, by using double luciferase bicistronic vectors, the presence of internal ribosome entry sites (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 53 publications
1
58
0
Order By: Relevance
“…Furthermore, our previous study has shown a high conservation of the FGF-1 IRES A secondary structure and function in mammals. 14 Our data suggest that the FGF-1 IRES is muscle specific. The FGF-1 IRES activity would require specific IRES trans-acting factors (ITAFs) to work efficiently, as shown for other cellular IRESs.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Furthermore, our previous study has shown a high conservation of the FGF-1 IRES A secondary structure and function in mammals. 14 Our data suggest that the FGF-1 IRES is muscle specific. The FGF-1 IRES activity would require specific IRES trans-acting factors (ITAFs) to work efficiently, as shown for other cellular IRESs.…”
Section: Discussionmentioning
confidence: 62%
“…As observed previously with plasmids transfected in the same cell line, the activity of the FGF-1 IRES was about three to four times lower to that of the EMCV IRES (Figure 1c). 14,15 C2C12 mouse myoblasts were transduced by the same virions. Transduction was less efficient than with 911 cells: an MOI of 10 5 was necessary to obtain a detectable luciferase expression (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IRES-containing mRNAs mostly encode regulatory proteins such as, e.g., growth factors and transcription factors. Several studies have reported that under stress conditions, where cap-dependent translation is blocked, translation of specific mRNAs is enabled through IRES elements ( [270] and references therein). Another function of IRESs involves the control of alternative initiation of translation.…”
Section: Important Regulatory Motifs In Utrs Of Mrnasmentioning
confidence: 99%